Alkaloid profile of leaves and seeds of lupinus hintonii C. P. Smith - Bermúdez Torres, Kalina; Wink, Michael (Zeitschrift für Naturforschung. C, a journal of biosciences, 2014)
L. hintonii C. P. Smith grows in the Central Highland forests of Mexico at altitudes between 2800 m to 3200 m above see level. Members of the genus Lupinus produce quinolizidine alkaloids as main chemical defensive compounds against herbivores. Surprisingly alkaloid profiles are rather constant within this species, while substantial variation was found when compared to morphologically closely related other taxa. As part of a phytochemical project on Mexican wild lupins, we report on the alkaloid profiles of seeds and leaves of L. hintonii. 19 alkaloids could be identified by capillary GLC-MS. Six major alkaloids occurred in leaves and seeds: 13-hydroxylupanine (28% and 45% respectively), tetrahydrorhombifoline (31% and 23% respectively), angustifoline (2% and 4% respectively), lupanine (7% and 5% respectively), 13α-tigloyloxylupanine (19% and 5% respectively) and 4α-angeloyl-3β-hydroxylupanine (9% and 2%). This chemical pattern resembles that of the North American lupin L. floribundus
Gesehen am 05.10.2017